The Social Structure of Peasent Community and Its Implicationto Welfare Differentiation.A case Study on Cocoa Peasant Community in Central Sulawesi and Nangroe Aceh Darussalam - Undang Fajar; MTF Sitorus; AH Darmawan; S.M.P. Tjondronegoro (Indonesian Coffee and Cocoa Research Institute, 2008)
The development of commercial crop cocoa have altered the structure of agrarian : from collective owners to individual owners. For the cocoa peasant communities, the agrarian resources are a base of their life. So, the changing of agrarian structure gives a way to changing process of the social structure community. This research means to analyze the social structure that emergence on cocoa peasant community and the implication of it to the differentiation of peasant welfare. The result of this research indicate that the inequalities of agrarian resources control on cocoa peasant communities have developed the form of peasant community social structure : “stratification which progressively unequal”. Furthermore, these social structure have implication to the increasing of welfare differentiation. In this case, a cocoa peasant community divided to three levels, that is: rich farmer (upper level), middle farmer (middle level), and the poor farmer (low level). The result of research also indicates that on Outside Java generally owning a lower agrarian density – the landless and he poor farmer have been occur, and the poor farmer not only lay at land less farmer (tunakisma) but also on an owner farmer. Base on gini ratio analysis, the equality of agrarian resource ownership generally have resided in high level. Even though, the equality of farmer household income and farmer household expenditure generally have resided in low level.Key words: social structure, welfare differentiation, peasant, cocoa.